P(NIPAM-co-AA)@BMMs with mesoporous silica core and controlled copolymer shell and its fractal characteristics for dual pH- and temperature-responsive performance of ibuprofen release. Issue 3 (11th February 2018) - Jin, Xiaoqi; Wang, Qian; Sun, Jihong; Panezai, Hamida; Bai, Shiyang; Wu, Xia
ABSTRACT: A kind of core–shell hybrid composite (P@BMMs) as a drug carrier was prepared through seed polymerization method, in which, biomodal mesoporous materials (BMMs) as core and copolymer poly( N -isopropylacryl-acrylamide)- co -poly(acrylicacid) [P(NIPAM- co -AA)] with pH- and temperature-responsive characteristics as shell. Its structural features and textural parameters were characterized using various techniques. The kinetic and thermodynamic evaluation demonstrated the existence of hydrogen bond interaction between IBU and P(NIPAM- co -AA)-coated surfaces. Meanwhile, the smart thermo/pH-responsive properties of ibuprofen (IBU) release could be regulated through adjusting coated amount of copolymer. Specially, the responsive properties of P@BMMs were traced by small-angle X-ray scattering technique, suggesting the surface roughness and structural irregularities. GRAPHICAL ABSTRACT: